2000
DOI: 10.1155/2000/141934
|View full text |Cite
|
Sign up to set email alerts
|

Fluid‐Structure Interaction Mechanisms for Close‐In Explosions

Abstract: This paper examines fluid-structure interaction for close-in internal and external underwater explosions. The resulting flow field is impacted by the interaction between the reflected explosion shock and the explosion bubble. This shock reflects off the bubble as an expansion that reduces the pressure level between the bubble and the target, inducing cavitation and its subsequent collapse that reloads the target. Computational examples of several close-in interaction cases are presented to document the occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
75
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 6 publications
9
75
0
Order By: Relevance
“…The mass exchange inside the cavitation region has to be introduced and a proper model has yet to be developed [10]. Although the cavitation zone may be simply treated by assuming a constant-pressure zone [4,11], this may result in inaccurate ow physics since subsequent wave cannot propagate through the said region and furthermore conservation laws are not maintained. In the present work, the simulation is carried out until the ow exhibits and sustains a pressure ÿeld slightly below the critical pressure (SVP of water), which indicates the likely presence of a cavitating region.…”
Section: Introductionmentioning
confidence: 99%
“…The mass exchange inside the cavitation region has to be introduced and a proper model has yet to be developed [10]. Although the cavitation zone may be simply treated by assuming a constant-pressure zone [4,11], this may result in inaccurate ow physics since subsequent wave cannot propagate through the said region and furthermore conservation laws are not maintained. In the present work, the simulation is carried out until the ow exhibits and sustains a pressure ÿeld slightly below the critical pressure (SVP of water), which indicates the likely presence of a cavitating region.…”
Section: Introductionmentioning
confidence: 99%
“…Further indications supporting this explanation can be seen in the following section where t shift is found to become larger as the size of the field bubbles increases and as the natural period of oscillation of the bubble increases. This finding cannot be captured by methods assuming homogeneous medium, e.g., (Wardlaw & Luton, 2000, Wardlaw & Luton, 2003 and the analytical Gilmore equation (Gilmore, 1952). This highlights the importance of considering the individual bubble dynamics in the dispersed phase for high fidelity modeling.…”
Section: Pressure and Density Variations In The Neighborhood Of The Pmentioning
confidence: 99%
“…Eulerian-Lagrangian approaches are more appropriate for higher void fractions (Spelt & Biesheuvel, 1997, Balachandar & Eaton, 2010, Raju et al, 2011, Shams et al, 2011. In a recent work by Raju et al (2011) comparing a continuum homogeneous model (Gilmore, 1952) , an Eulerian multicomponents model (Wardlaw & Luton, 2000, Wardlaw & Luton, 2003, and an Eulerian-Lagrangian model , Chahine, 2009, Hsiao et al, 2013b it was found that high-frequency local fluctuations were only captured when an Eulerian viscous solver was coupled with a Lagrangian discrete bubble dynamics and when the microscale behavior of the field bubbles was well resolved. Continuum models, on the other hand, captured well the average low-frequency behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The pressure fields in the fluid and at the specimen-water interface following detonation of an explosive sheet were calculated using a fully coupled Euler-Lagrange finite element hydrocode [Wardlaw and Luton 2000;Wardlaw et al 2003]. The code allowed the analysis of shock propagation through a fluid medium using an Eulerian solver and then coupled it to the structural response of the solid target using a Lagrange code.…”
mentioning
confidence: 99%
“…The Euler run was started with 0.2 mm cells in the explosive sheet thickness direction and 0.4 mm divisions in the other two directions (in the plane parallel to the explosive sheet). The explosive sheet was specified by its geometry, the explosive's material properties, and by the detonation velocity using the Jones-Wilkins-Lee equations of state for shock calculations [Wardlaw and Luton 2000;Wardlaw et al 2003]. The pressure loading on a rigid wall, representing the front surface of the solid cylinder, was calculated at four locations along the radial direction measured from the shortest distance of impact of the blast wave.…”
mentioning
confidence: 99%